Does smooth endoplasmic reticulum aggregation in oocytes impact the chromosome aneuploidy of the subsequent embryos? A propensity score matching study - Meng Wang; Limin Gao; Qiyu Yang; Rui Long; Yini Zhang; Lei Jin; Lixia Zhu (BMC, 2023)
Abstract Background The appearance of smooth endoplasmic reticulum aggregation (SERa) is one of the most common dysmorphic phenotypes of oocytes, however, the impact of SERa occurrence on in vitro fertilization (IVF) outcomes is controversial. This study aimed to investigate the impact of SERa in oocytes on the aneuploidy of the subsequent embryos in IVF. Methods In this retrospective cohort study, a total of 114 intracytoplasmic sperm injection (ICSI) cycles with the appearance of SERa undergoing preimplantation genetic testing for aneuploidy (PGT-A) were enrolled, and among them there were 323 SERa(+) oocytes and 1253 sibling unaffected oocytes. The 907 PGT-A cycles without SERa during the same period were enrolled as controls. A propensity score matching of 1:1 ratio between these two groups resulted in 113 matched cycles. The outcome parameters between the SERa(+) cycles/oocytes and the controls were compared. IVF laboratory outcomes, PGT-A outcomes, and clinical and neonatal outcomes were the main outcomes. Results Increased abnormal fertilization rate and reduced blastocyst formation rate can be observed in both SERa(+) cycles and oocytes, some other parameters on developmental potential, such as available embryo rate at Day 3 and available blastocyst rate, were also impaired in the case of SERa occurrences. Among the 910 blastocysts for PGT-A, the percentage of euploid embryos was similar between the matched cohorts, while an unpredicted increase of the proportions of euploid in the SERa(+) oocytes, compared to the SERa(-) oocytes. Moreover, there was no significance in terms of clinical and neonatal outcomes, such as implantation rate, biochemical pregnancy rate, clinical pregnancy rate, miscarriage rate, and live birth rate, regardless of the presence of SERa in cycles and oocytes. Conclusions The appearance of SERa within mature oocytes has no significant impact on the aneuploidy of subsequent blastocysts. It is recommended to utilize these oocytes, especially for those with few oocytes or advanced maternal age, which is likely to increase the cumulative pregnancy rate. This study may offer evidence to assist embryologists to make clinical decisions concerning SERa(+) oocytes more consciously and rationally.